Shocks, Individual Risk Attitude, and Vulnerability to Poverty among Rural Households in Thailand and Vietnam. (July 2015) - Gloede, Oliver; Menkhoff, Lukas; Waibel, Hermann
Summary: We examine whether the experience of shocks influences individual risk attitude. We measure the risk attitude of more than 4, 000 households in Thailand and Vietnam via a simple survey item. The experience of adverse shocks, which is typical for poor and vulnerable households, is related to a higher degree of risk aversion, even when controlled for a large set of socio-demographic variables. Therefore, shocks perpetuate vulnerability to poverty via their effect on risk attitude. We extend this general finding to various categories of shocks and find differences between Thailand and Vietnam. This suggests that risk-coping strategies profit from case-specific design.